Prenatal and Intrapartum Factors Associated With Infant Temperament: A Systematic Review - Takegata, Mizuki; Matsunaga, Asami; Ohashi, Yukiko; Toizumi, Michiko; Yoshida, Lay Myint; Kitamura, Toshinori (Frontiers in Psychiatry, 2021)
Abstract Background: Temperament involves an individual’s variation in behavioural tendencies of emotional responses and reaction to the stimuli that appear after birth. Because ‘foetal programming’ is a strong hypothesis in developing temperament, prenatal and intrapartum factors may be significant determinants for infant temperament. This systematic literature review aims to elucidate the evidence of prenatal and intrapartum predictors, including genetic, biological, environmental, socio-demographic, psychological and obstetric factors of parents and their child. Methods: Relevant articles were searched using MEDLINE, PubMed and SCOPUS. The inclusion criteria were (a) an original research article, (b) written in the English language, (c) assessed temperament of infants who were 12 months old or less as an outcome variable, and (d) investigated prenatal and intrapartum factorial variables of infant temperament. Following the PRISMA guideline, articles found on the three databases were screened and selected according to the inclusion and exclusion criteria before the final review. Results: Finally, 37 articles were reviewed. This systematic review identified a variety of prenatal and intrapartum factors that were significantly associated with infant temperament: (1) genetic and biological factors: certain genotypes, maternal cortisol and ACTH, CRHs, (2) environmental factors: substance use such as tobacco, alcohol and illegal drugs, (3) socio-demographic factor: lower-income, (4) psychological factors: depression or anxiety, eating disorders, personality types of mothers, and domestic violence, and (5) obstetric factors: foetal growth (birth weight), hypertension among mothers, nausea (emesis), and preterm birth. Conclusion: These findings support the gene-environment interaction and biological mechanisms for developing infant temperament, suggesting the importance of ensuring a safe and comfortable environment for pregnant mothers, unborn child and families during pregnancy and delivery.